Two simultaneous intussusceptions in a neonate with DiGeorge syndrome: A case report - Uday Bhaskar MNS Mokrala; Lakshmi Sundararajan; Chandra Kumar Natarajan (EL-Med-Pub, 2021)
Background: Double simultaneous intussusception is a peculiar and rare variety of intussusception with only 3 previously reported neonatal cases. Case presentation: A 15-day-old male neonate with respiratory distress was found to have Tetralogy of Fallot and hypoplastic pulmonary stenosis. Small bowel intussusception was diagnosed on ultrasound abdomen following hematochezia on the next day. Emergency laparotomy revealed two intussusceptions, ileocolic and jejunojejunal, with bowel gangrenous requiring resection and anastomosis. No pathological lead point was identified. He recovered with supportive care and was discharged. Conclusion: Simultaneously occurring double intussusceptions are extremely rare in neonates, and thorough examination of the entire small bowel in cases of intussusception is key to the diagnosis.